Penerapan Metode Fuzzy Simple Additive Weighting Dalam Penilaian Kinerja Pegawai Terbaik - Gustian, Dudih; Dzikril, Tubagus (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Employee performance is the result obtained after someone performs their tasks or work in accordance with the standards set in the company. Evaluation is not only intended to assess and improve poor performance, but also to encourage employees to work better. This study uses the Simple Additive Weighting (SAW) method with the Trade and Industry Department as its case study to solve the problem of evaluating the performance of employees at the Trade and Industry Department. The Simple Additive Weighting (SAW) method is one of the methods used in the decision-making process. The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The SAW method requires the normalization of the decision matrix (X) to a scale that can be compared with all the existing alternative ratings. One application of the Simple Additive Weighting (SAW) method is the selection of high-performing employees. The goal of this study is to choose the best employees at the Trade and Industry Department and to control the performance of employees at the Trade and Industry Department in order to reach the targets that have been set.